Sea cucumbers crackers, Nutritious Snacks That Are Safe for Consumption and Can Treating Constipation - Tutik Wahyuni; Sunarto Sunarto; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2012)
The objective of this study is to find the dose of sea cucumber crackers that can cope constipation and determine levels of nutrients, fiber as well as mercury sea cucumber crackers. Research design was quasi-experimental study. Subjects of this study was the new student, which are grouped into 3 dose groups: 15, 30 and 45 g. Inclusion criteria was willing to follow the research, defecation constipation, not allergies are sea fish, not the cure constipation, no diarrhea, no fasting. Defecation event before and after consumption of crackers, given feces type based on the standard scale